(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
The purpose of this article is to relate the terms of educational innovation with the problem-solving technique. When an educational innovation is planned, it should determine which is the area, action, and moment where it would be develop, to generate the expected impact. That is how the technique allows people a strategy to identify the problem and its possible solutions that will promote innovation. This article was composed by consulted bibliography as part of an innovation process of the Master’s degree program of Technology and Educational Innovation at Universidad Nacional of Costa Rica. Keywords: educational innovation, investigation, problem solving, metacognition, self-evaluation.